Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Pengungkapan Manajemen Risiko : (Studi Pada Perusahaan Sub Sektor Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022) - Isynuwardhana, Deannes; Parmita, Ida Bujangga Ayu Diah (eProceedings of Management, 2024)
The object of research is the telecommunications sub-sector industry listed on the Indonesia Stock Exchange from 2019-2022.2022. This study aims to determine whether independent factors such as the number of independent commissioners, audit committee, risk management committee, and company size affect the disclosure of telecommunication subsectors.independent commissioners, audit committee, risk management committee, and company size affect risk management disclosure.risk management disclosure. In this study, twelve samples were used, so a total of 48 samples were used. Purposivesampling was used according to certain standards, and Eviews-12 was used as a tool to perform panel data regression and descriptive statistical analysis.panel data regression and descriptive statistical analysis. The results show the risk management committee, audit committee, risk management committee, and independent supervisory committee.risk management committee, and independent supervisory committee simultaneously affect risk management disclosure.disclosure. However, partially, only the risk management committee has a positive effect on companies listed on the IDX during the 2019-2022 period.listed on the IDX during the 2019-2022 period. Keywords- audit committee, risk management committee, proportion of independent board of commissioners, riskmanagement disclosure